Polymorphism of PIT‐1, PRL and GH genes in dairy cattle of the Caucasian Brown breed bred in various natural ecological zones of the Republic of Dagestan, Russia - A. A. Ozdemirov; M. I. Selionova; L. N. Chizhova; A. A. Khozhokov; E. S. Surzhikova; D. M. Ramazanova (Юг России: экология, развитие, 2020)
Aim. The widespread use of so‐called commercial breeds leads to the loss of a unique gene pool of native breeds and the narrowing of the genetic base that is necessary to preserve and to increase the genetic diversity of cattle breeds which are still preserved. These breeds include the Caucasian Brown. In connection , the aim of this research was to study the polymorphism of PIT‐1, PRL and GH genes in dairy cattle bred in different ecological climatic zones of the Republic of Dagestan to identify the genotypes of carriers of selection‐significant marker alleles for their preservation and further use in the selection process.Material and Methods. Genotyping of the Caucasian brown breed cows bred in different natural climatic zones was carried out using PCR‐RFLP methods. The polymorphism of PIT‐1, PRL and GH genes was studied, population analysis of their distribution in the cattle stock studied was carried out and the features of the genetic structure in the researched populations were studied in relation to the conditions of their habitat.Results. The specific allelic PIT‐1, PRL, and GH gene spectrum, characteristic for each animal population studied has been established. Homozygous and heterozygous carrier genotypes of the desired marker alleles with frequency of occurrence depending on both the gene and the animal population were identified. The genetic structural features of the genes studied in the researched populations were revealed.Conclusion. The data obtained indicate the genetic uniqueness of the Caucasian Brown breed bred in different natural climatic zones in the Republic of Dagestan and are probably associated with the manifestation of adaptations, the nature of which has developed under the influence of the prevailing ecological, natural climatic conditions of its habitat.